Model Penduga Produksi Kopal - Wien Setya Budhi Irawan; Endang Suhendang; Juang Rata Matangaran (Jurnal Manajemen Hutan Tropika, 2007)
The objective of this study was to find out the prediction model  for copal production (Y) by  the use of prediction variables. The variables were diameter (X1), bark thicknesses (X2), stand density (X3), slope (X4), and direction of the slope (X5). The study was conducted at Senduro Forest District, Probolinggo Forest Management Unit of Perum Perhutani, Unit II East Java. Data was collected from 80 sample trees of Agathis loranthifolia Salibs which were tapped on August 2006.  The  result of the study showed that there were several  regression prediction models  for  copal production:  doubled linear, multiplicative, exponential and quadratic regression models. Multiplicative regression model with the highest  R2-adj  value was  then chosen  as the best prediction model  for  copal production.  Thereby, production estimation model of copal production of Agathis loranthifolia Salis. was  LogY = 0.397 + 1.54 LogX1 + 0.496 LogX2  -  0.528 LogX3 + 0.201 LogX4  ; or Y = 2.4945X11.54X20.496X3-0.528X40.201; R-Sq =84.7%, R-Sq(Adj) = 83.7%.  Keywords:  multiplicative regression model, copal, diameter, bark thickness, stand density, slope